PENAMBAHAN IKAN LELE (CLARIAS GARIEPINUS) DAN ISOLATED SOY PROTEIN TERHADAP DAYA TERIMA DAN KADAR PROTEIN CILOK - Sri Lestari; Annis Catur Adi (Media Gizi Indonesia, 2016)
Some research found that p rotein adequacy from snack for elementary school children are still lacked. Snacks availability at schools have an important role to fulﬁ ll  protein requirement  for students. The purpose of this research was to analyze the effect of  catﬁ sh (Clarias gariepinus) and Isolated Soy Protein (ISP) addition on    acceptance level and p rotein content of c ilok (snack). Research methods used for formula development was experimental research with completely randomized design. Repetition was performed four times on ﬁ ve treatments (one control and four modiﬁ cations, those are F1 was added ISP, F2 was added c atﬁ sh, F3 was added c atﬁ sh ﬂ our, and F4 was added c atﬁ sh and ISP). Assessment of a  cceptance used hedonic test. Variable in this research was a  cceptance level (color, aroma, texture, and ﬂ avor) and p rotein content. Hedonic test was performed to 71 students. The difference of a  cceptance (color, aroma, texture, and ﬂ avor) between 5 formulas was tested used Cochran’s Q; the difference within formula then analyzed by Mc Nemar test. Hedonic test result showed that panelists preferred F0. F4 had highest p rotein level based on DKBM and laboratory analysis found  protein level (9.4 g/ 100 g) higher than recommended value. Cochran’s Q test showed signiﬁ cant difference a  cceptance on color (p = 0.002) and taste (p = 0.047). Mc Nemar test showed the difference within formula on the color was F0 with F3, F1 with F3, and F2 with F3, while difference ﬂ avor formula found in F0 with F3. This research concluded that F4 had the highest p rotein level but the a  cceptance was still low, it is recommended to modify F4 so that it become more acceptable but did not change the  protein content.